Achieving the desired transformer leakage inductance necessary in DC-DC converters for energy storage applications - De, D.; Klumpner, Christian; Rashed, Mohamed; Patel, C.; Kulsangcharoen, P.; Asher, Greg (2012)
This paper presents a cost effective winding design and evaluation of a medium frequency isolation transformer typically used in bidirectional isolated DC/DC converters. Since leakage inductance and winding resistance of a high frequency transformer are interdependent, any attempt to increase the leakage inductance by adjusting the winding arrangement increases the resistance as well and impacts the efficiency. This paper proposes the use of flux diverter caps made of a relatively small amount of ferrite material to get the desired value of inductance whilst maintaining the losses in the windings at reasonable levels. The proposal is experimentally evaluated on a 5kW prototype.